Komunikasi Instruksional Guru Keterampilan Dalam Meningkatkan Kemampuan Membatik Pada Siswa Tunarungu Jenjang Sekolah Menengah Atas (SMA) Di Sekolah Luar Biasa Negeri Pembina Kota Pekanbaru - Erdiyanto, Erdiyanto (Komunika : Jurnal Ilmiah Komunikasi, 2024)
This study investigates Teacher Instructional Communication Skills in Improving Batik Skills in Deaf Students at Senior High School (SMA) in Special Schools for the Special Needs of State Pembina Pekanbaru City. Batik is one of the skills taught to students, one of which is to Deaf students. To develop this skill, one of which is through Instructional communication. The research method used is descriptive qualitative method. The results of the study indicate that in improving the batik skills of deaf students at SLBN Pembina Pekanbaru, teachers use total instructional communication methods with projector media, batik tools and materials, textbooks and sign language. In addition, to improve students' batik skills, teachers also conduct ability and interest tests so that there is no coercion to follow the batik skills. Although obstacles are found from the students themselves, such as differences in student personality which sometimes cause differences in perception, teachers always try to find ways to convey information well and can be easily accepted by students.